Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae) - Early, John W.; Masner, Lubomír; Johnson, Norman F. (Zootaxa, 2007)
The genus Archaeoteleia Masner is revised and redescribed. Five new species from New Zealand and six from Chile are described: A. chambersi Early, new species, A. gilbertae Early, new species, A. karere Early new species, A. onamata Early, new species, A. waipoua Early, new species, A. dispar Masner, new species, A. penai Masner, new species, A. puncticeps Masner, new species, A. robusta Masner, new species, A. simulans Masner, new species, and A. submetallica Masner, new species. The previously unknown females of A. mellea Masner and A. pygmea Masner are described from Chile. The genus is probably more closely related to Scelionini sensu lato than to the other putatively plesiomorphic genera Nixonia Masner (Nixoniini), Sparasion Latreille and Sceliomorpha Ashmead (Sparasionini s. str.), and Neuroscelio Dodd (Gryonini). Archaeoteleia chambersi, new species, and A. novaezealandiae Masner parasitize eggs of Gymnoplectron spp. (Orthoptera: Rhaphidophoridae, Macropathinae). Both Archaeoteleia and Macropathinae have austral disjunct distributions and are considered to be Gondwanan relicts.